Design of a Digital Ethnomathematics Module Based on Augmented Reality: A Study on Geometric Concepts Through the Exploration of the Mande Karesemen for Elementary Schools - Maharbid, Dian Anggraeni; Herman, Tatang; Agustin, Mubiar; Riyana, Cepi (KnE Social Sciences, 2025)
This study presents the design of a digital ethnomathematics module using augmented reality (AR) to enhance the learning of geometric concepts for elementary school students, integrating local cultural elements from the Mande Karesemen at Keraton Kesepuhan, Cirebon. Employing the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, the research focuses on developing an interactive module that aligns with students’ cognitive development and curriculum standards, specifically targeting 4th and 5th-grade students. The module incorporates threedimensional (3D) models of cultural artifacts, enabling students to explore and visualize shapes, symmetry, area, and perimeter in a culturally contextualized manner. The AR feature allows students to engage with the historical and cultural aspects of the Keraton Kesepuhan, experiencing architectural designs that embody geometric concepts. Additional features include AR-based virtual tours, narrated instructions, gamified quizzes, and offline accessibility, fostering a deeper connection between mathematical concepts and cultural heritage. By facilitating active exploration, the module helps bridge the gap between abstract mathematical principles and tangible, real-world examples. This innovative approach addresses challenges in elementary mathematics education by improving student engagement, understanding, and cultural awareness through an immersive and meaningful learning experience, making mathematics more relevant and accessible to students by incorporating their local culture and heritage into the learning process.